2021
DOI: 10.1186/s12936-021-03732-z
|View full text |Cite
|
Sign up to set email alerts
|

From informed consent to adherence: factors influencing involvement in mass drug administration with ivermectin for malaria elimination in The Gambia

Abstract: Background The World Health Organization (WHO) recommends consideration of mass drug administration (MDA) for malaria control in low-endemic settings approaching elimination. However, MDA remains a controversial strategy, as multiple individual, social, and operational factors have shown to affect its acceptability at local levels. This is further complicated by inconsistent definitions of key indicators derived from individual and community involvement—coverage, adherence, and compliance—that … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…Moreover, participants had experience of previous antimalarial pills, and they were concerned about drug adverse reactions, and others were reluctant to take drugs without malaria symptoms. These barriers have also been documented in previous studies [18,[21][22][23][24]. Furthermore, like previous studies [25] have reported, lack of access to accurate information, spread of misinformation about malaria intervention, being unable to drink alcohol while taking DHAp [7], lack of PLOS ONE trust of fieldworkers, and the demand of food as precondition to take DHAp are potentials barriers to rfMDA.…”
Section: Discussionsupporting
confidence: 56%
“…Moreover, participants had experience of previous antimalarial pills, and they were concerned about drug adverse reactions, and others were reluctant to take drugs without malaria symptoms. These barriers have also been documented in previous studies [18,[21][22][23][24]. Furthermore, like previous studies [25] have reported, lack of access to accurate information, spread of misinformation about malaria intervention, being unable to drink alcohol while taking DHAp [7], lack of PLOS ONE trust of fieldworkers, and the demand of food as precondition to take DHAp are potentials barriers to rfMDA.…”
Section: Discussionsupporting
confidence: 56%
“…One study required women of reproductive age to undergo pregnancy testing; both the production of the urine specimen for testing in places where a private toilet was not available and reading of the test result in a public place created privacy concerns, leading to decreased participation among this group. 36 Ethnicity was related to willingness to participate in MDA. 40 One study noted that ethnic minorities were potentially underrepresented because of geographic distribution rather than direct discrimination and also found that some portions of the population relied on traditional medicine because of affordability more so than any other reason, which led to less familiarity with MDA and thus to lower participation.…”
Section: Resultsmentioning
confidence: 99%
“…It might be anticipated that exclusion criteria related to pregnancy or breastfeeding would affect the uptake of ivermectin, however a similar phenomenon would not be expected for DHP. Previous studies have highlighted that not receiving ivermectin during previous pregnancies can encourage women not to participate to the MDA even if not pregnant [ 20 , 21 ], alternatively some women may have not wanted to complete a pregnancy test due to a lack of privacy [ 22 ]. Men have also been reported to be more likely to receive MDA for soil transmitted helminths in Kenya but no difference between sexes was seen amongst children in a previous study examining participation in trachoma MDA in the Gambia or in adults for soil-transmitted helminths in Uganda [ 3 , 6 , 23 ].…”
Section: Discussionmentioning
confidence: 99%